"If You Want the History of a White Man, You Go to the Library" 1: Critiquing Our Legacy, Addressing Our Library Collections Gaps. Issue 3 (2nd October 2017) - Bowers, Jennifer; Crowe, Katherine; Keeran, Peggy
ABSTRACT: In 1864, the same year the University of Denver was founded by John Evans, then the territorial governor of Colorado and the superintendent of Indian affairs, a group of U.S. militia attacked and killed vulnerable members of the Cheyenne and Arapaho nations at Sand Creek. Using critical race theory and the feminist "ethic of care, " we critique our collections in terms of the massacre and absent Native American voices in order to develop a collecting philosophy and direction to acknowledge and address the gaps and to formulate strategies for teaching students to interrogate a predominately white institutional archive to give voice to the absent or silenced.